Anti-inflammatory steroids from the stems of Solanum nigrum L. (June 2023) - Deng, Junru; Wang, Lin; Jin, Qingyu; Zeng, Jia; Xu, Jingwen; He, Xiangjiu; Wang, Yihai
Abstract: Sixteen previously undescribed steroidal sapogenins along with two known ones were isolated from the stems of Solanum nigrum L. (Solanaceae). Their structures were identified using a combination of 1D and 2D NMR, HR-ESI-MS spectroscopy, the Mosher method, and X-ray diffraction analysis. Compounds 1 –8 have an unusual F ring and 9 –12 have a derived A ring, both of which are rare skeletons found in natural products. The biological evaluation showed that the isolated steroids exhibited inhibition of nitric oxide in the LPS-induced RAW 264.7 macrophages with IC50 values from 7.4 to 41.3  μ M. Further studies revealed that compounds 6 and 10 exhibited anti-inflammatory activity by blocking the nuclear translocation of NF- κ B, and down-regulating the expression of iNOS, COX-2, IL-1 β, and IL-6 in a concentration-dependent manner. These results suggest that the stems of S. nigrum may serve as a source of anti-inflammatory agents for use in healthy or medicinal products. Graphical abstract: Sixteen previously undescribed steroidal sapogenins along with two known ones were isolated from the stems of Solanum nigrum L. Image 1 Highlights: Sixteen undescribed steroids were isolated and identified from Solanum nigrum L. Compounds 1 –8 have unusual F ring and 9 –12 bearing derived A ring. Compounds 6 and 10 suppressed the expression of iNOS and COX-2. The stem of S. nigrum may be a good source of anti-inflammatory agent.